Sequencing of Entamoeba Histolytic Cysteine Protease 5 (CP5) Isolated from Diarrheic Cases in Babylon Province - Hayam K. Al- MasoudI (Journal of Global Pharma Technology, 2018)
The results of the current study revealed that the amplified DNA for cysteine proteinase (CP5) in 40 cases .The characterization of the cysteine proteinase which is the most important virulence factors secreted by E. histolytica have led to a better understanding the pathogenic mechanisms of E. histolytica (pathogenic ) are distinct species from the nonpathogenic or a harmless commensal.